Soft Skills in Language Education: From Perception to Frequency of Instruction - Rahate Ellah, Hicham; Azmi, Noureddine (International Journal of Language and Literary Studies, 2024)
In today’s interconnected world, the teaching and learning of soft skills or as other researchers call them the 21st skills has become very important for Moroccan students to develop. The integration of these skills into the curriculum has become an urgent need that should be met immediately. In other words, teachers in general and English language teachers in particular are in the most appropriate position to help their students improve these skills. Unfortunately, research shows that the focus is still on teaching students technical skills more than soft ones. In this regard, this study aims to explore the extent to which EFL teachers are aware of the importance of soft skills education and to identify the frequency of teaching soft skills in the EFL classroom. This study used a quantitative method to collect numerical data to answer the main research questions. It implemented a questionnaire as the main tool for data collection. The participants were teachers of English from different public and private schools in Morocco. Research findings show that though teachers are aware of the importance of soft skills education and can teach them, they rarely help their students develop these skills for many reasons. The findings also reveal that English language teachers still need training in soft skills teaching and assessment.